2016
DOI: 10.1016/j.jtcme.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Patients' preference for integrating homeopathy (PPIH) within the standard therapy settings in West Bengal, India: The part 1 (PPIH-1) study

Abstract: There is lack of studies assessing the preference of Indian patients for integration of homeopathy into standard therapy settings. The objectives of this study were to examine the knowledge, attitudes, and practice of homeopathy among Indian patients already availing homeopathy treatment and its integration into mainstream healthcare.A cross-sectional survey was conducted among adult patients attending the out-patients of the four government homeopathic hospitals in West Bengal, India. A self-administered 24-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Collaborative pilot projects of homeopathic integration in the National Programme for Prevention and Control of Cancer, Diabetes, Cardiovascular Diseases & Stroke (NPCDCS) are being initiated by the Department of Health & Family Welfare, Ministry of AYUSH, and Central Council for Research in Homeopathy. Further details of homeopathy infrastructure at the state and national level are elaborated elsewhere …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collaborative pilot projects of homeopathic integration in the National Programme for Prevention and Control of Cancer, Diabetes, Cardiovascular Diseases & Stroke (NPCDCS) are being initiated by the Department of Health & Family Welfare, Ministry of AYUSH, and Central Council for Research in Homeopathy. Further details of homeopathy infrastructure at the state and national level are elaborated elsewhere …”
Section: Discussionmentioning
confidence: 99%
“…Results obtained from the first study (part 1) are reported elsewhere . This paper presents the results of the second study (part 2).…”
Section: Introductionmentioning
confidence: 99%
“…The Bengali questionnaire was already available and has been used earlier. 19 It included 2 sections: sociodemographic information and 25 questions assessing the patient’s knowledge, attitudes, and practice of homoeopathic medicine and its integration into the existing hospital services. Sociodemographic data sought information regarding age, sex, marital status, employment status, monthly household income, and educational level.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…However, patients’ preference for the integrated services remains underresearched in India. Earlier, PPIH-1 and PPIH-2 studies were undertaken in West Bengal assessing preference for integrated services of the patients already availing services from homoeopathy hospitals (PPIH-1) 19 and evaluating satisfaction of patients from integrated services (PPIH-2). 20 The PPIH-1 survey revealed favorable attitude toward integrating homoeopathy into conventional health care settings among the patients attending the homoeopathic hospitals in West Bengal, India.…”
mentioning
confidence: 99%
“…A study was carried out recently among 1352 patients in West Bengal with the aim of learning whether patients would like homoeopathy to be integrated with the standard therapy. Forty per cent of the respondents felt that homoeopathy can be used side by side with standard therapy; 68.2% used homoeopathic medicine; and 76.6% used it to treat their children's ailments (15). The universality of the AYUsH systems of medicine has become clearly evident since the implementation of the NRHM.…”
Section: Universalitymentioning
confidence: 99%